2020
DOI: 10.1029/2020gl088743
|View full text |Cite
|
Sign up to set email alerts
|

Robust Enhancement of Tropical Convective Activity by the 2019 Antarctic Sudden Stratospheric Warming

Abstract: Tropical tropospheric responses to a sudden stratospheric warming (SSW) event that occurred over Antarctica in September 2019 have been investigated by conducting a series of ensemble forecast experiments. Comparative examinations between the normal forecast and the partially nudged forecast, whose stratospheric circulation is constrained to a reanalysis, reveal a significant enhancement/suppression in the convective activity (upwelling/downwelling) over the northern/southern part of the tropics. Such an accel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 60 publications
(76 reference statements)
3
29
0
Order By: Relevance
“…The observational finding noted in the present study on the effect of northern hemispheric SSW events on the convection and rainfall events observed in winter at Cochin, a southern region of the Asian summer monsoon, agrees very well with the outcome of the ensemble forecasting experiments by Noguchi et al. (2020).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The observational finding noted in the present study on the effect of northern hemispheric SSW events on the convection and rainfall events observed in winter at Cochin, a southern region of the Asian summer monsoon, agrees very well with the outcome of the ensemble forecasting experiments by Noguchi et al. (2020).…”
Section: Resultssupporting
confidence: 92%
“…(2014) reported that the decrease in temperature in the UTLS region induces upward vertical motion in the equatorial troposphere that enhances convective activity. The enhanced Brewer‐Dobson circulation disrupts the tropical environment generates deep cumulus convection (Nagouchi et al., 2020). Bal et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the state of the Antarctic stratosphere during the 2019 winter and spring was unusual due to the large enhancement of the PWs. Noguchi et al (2020) observed the effect of 2019 unusual warming due to PW1 enhancement in the B‐D (Brewer‐Dobson) circulation through the tropical and polar stratosphere temperature change.…”
Section: Resultsmentioning
confidence: 99%
“…Variability in the Brewer-Dobson circulation driven by tropospheric waves can affect tropical upwelling, with implications for tropical convective patterns and precipitation 93 . For example, accelerations of the Brewer-Dobson circulation associated with SSWs lead to enhanced tropical upwelling 94,95 , which may reduce the static stability in the tropical tropopause layer and enhance SH tropical convection 96,97 (Fig. 2).…”
mentioning
confidence: 99%